(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this article is to examine library technical advancements and potential webbasedlibrary service developments. Library development from pre-existing media to today’s pervasivepresence is examined in this work. The study highlights potential library services that are available toeveryone. Based on an extensive analysis of the relevant literature, this research provides acomprehensive picture of the phenomena being studied. An important source of data utilised in this studywas the researchers’ first-hand knowledge of the library and information services industry, as well astheir regular discussions with colleagues in the IT area on how to improve library services offered online.Libraries and LIS workers may use the study’s findings to better prepare themselves for a web-basedinformation environment. New library services may be offered to college students by libraries andIbrarians as a result of this study.